Didactics and Inclusion in Mathematics Classrooms. Analysis of a Case in Chile - Filippi-Peredo, Cecilia; Aravena-Díaz, María (Revista Electrónica Educare, 2021)
The article shows through two central sections an educational theme of great relevance linked to special educational needs and how these have been addressed since the incorporation of special education into the regular classroom. The route of arguments that are being connected and that give structure to this text exposes foundations, concepts, experiences and reflections on a case studied, with the aim of contrasting the theoretical principles and the reality of the classroom, in relation to inclusive education and teaching practices, to finally deliver suggestions that favor the renewal of learning spaces and the inclusion of each student in math classes.